PERSEPSI GENERASI Z TERHADAP FITUR TIKTOK SHOP PADA APLIKASI TIKTOK - Ai Nur Sa’adah; Ayu Rosma; Dea Aulia (Transpublika Publisher, 2022)
TikTok is an application that is currently very popular with the public. This study aims to determine how Generation Z's perception of the TikTok Shop feature on the TikTok application is. The method in this study uses descriptive qualitative analysis of various conditions obtained from the results of interviews with the distribution of questionnaires in the form of google form. The sample in this study was 30 respondents. The indicators used are based on the technology accepted model (TAM) with indicators of perceived ease of use of technology, perceived benefits of technology and perceived risk to determine a person's behavioral intentions in using technology. The results indicate that generation Z has a perception of convenience showing 90% of generation Z agrees that the TikTok Shop feature provides a lot of convenience in its use, the perception of benefits shows that 85.56% of generation Z agrees that the TikTok Shop feature provides benefits for transaction activities, the perception of risk shows that 93.35% of Generation Z thinks that the TikTok Shop feature has little risk in its use. It can be concluded that Generation Z in utilizing the TikTok Shop feature is influenced by the perception of benefits, the perception of convenience and the perception of risk.